TGIF1 homeodomain interacts with Smad MH1 domain and represses TGF-β signaling. Issue 17 (28th July 2018) - Guca, Ewelina; Suñol, David; Ruiz, Lidia; Konkol, Agnieszka; Cordero, Jorge; Torner, Carles; Aragon, Eric; Martin-Malpartida, Pau; Riera, Antoni; Macias, Maria J
Abstract: TGIF1 is a multifunctional protein that represses TGF-β-activated transcription by interacting with Smad2-Smad4 complexes. We found that the complex structure of TGIF1–HD bound to the TGACA motif revealed a combined binding mode that involves the HD core and the major groove, on the one hand, and the amino-terminal (N-term) arm and the minor groove of the DNA, on the other. We also show that TGIF1–HD interacts with the MH1 domain of Smad proteins, thereby indicating that TGIF1–HD is also a protein-binding domain. Moreover, the formation of the HD-MH1 complex partially hinders the DNA-binding site of the complex, preventing the efficient interaction of TGIF1–HD with DNA. We propose that the binding of the TGIF1 C-term to the Smad2-MH2 domain brings both the HD and MH1 domain into close proximity. This local proximity facilitates the interaction of these DNA-binding domains, thus strengthening the formation of the protein complex versus DNA binding. Once the protein complex has been formed, the TGIF1-Smad system would be released from promoters/enhancers, thereby illustrating one of the mechanisms used by TGIF1 to exert its function as an active repressor of Smad-induced TGF-β signaling.